Nanocarriers containing platinum compounds for combination chemotherapy - Fang, Guihua; Zhang, Aiwen; Zhu, Lu; Wang, Qiuxiang; Sun, Feilong; Tang, Bo (Frontiers in Pharmacology, 2022)
Platinum compounds-based drugs are used widely in the clinic for the treatment of many types of cancer. However, serious undesirable side effects and intrinsic or acquired resistance limit their successful clinic use. Nanocarrier-based combination chemotherapy is considered to be an effective strategy to resolve these challenges. This review introduces the recent advance in nanocarriers containing platinum compounds for combination cancer chemotherapy, including liposomes, polymer nanoparticles, polymer micelles, mesoporous silica nanoparticles, carbon nanohors, polymer-caged nanobins, carbon nanotube, nanostructured lipid carriers, solid lipid nanoparticles and multilayered fiber mats in detail.